2011
DOI: 10.1007/s11605-011-1687-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Phase Computed Tomography for Assessment of Pancreatic Fibrosis and Anastomotic Failure Risk Following Pancreatoduodenectomy

Abstract: Pancreatic CT enhancement pattern can accurately assess pancreatic fibrosis and is a powerful tool to predict the risk of developing a clinically relevant PAF following PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 31 publications
(95 reference statements)
3
42
1
13
Order By: Relevance
“…This is not the first study which claims that we can estimate the pancreatic texture with preoperative CT evaluation. Hashimoto et al 28 reported that hepatic to pancreatic phase, late/ early ratio which is calculated in contrast to enhanced CT is significantly related with POPF after PD. Kirihara et al 29 reviewed 173 consecutive patients undergoing PD and found a significant relationship between subcutaneous and visceral adipose tissue areas, and skeletal muscle area calculated from preoperative CT can be used to predict the occurrence of POPF after PD.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the first study which claims that we can estimate the pancreatic texture with preoperative CT evaluation. Hashimoto et al 28 reported that hepatic to pancreatic phase, late/ early ratio which is calculated in contrast to enhanced CT is significantly related with POPF after PD. Kirihara et al 29 reviewed 173 consecutive patients undergoing PD and found a significant relationship between subcutaneous and visceral adipose tissue areas, and skeletal muscle area calculated from preoperative CT can be used to predict the occurrence of POPF after PD.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, the SI ratio ≥1.1 was the only preoperative parameter that could predict the leakage. Using a dual-phase pancreatic CT technique, Hashimoto et al expressed the late phase/early phase ratio (L/E ratio), calculated as (hepatic phase—unenhanced phase)/(pancreatic phase—unenhanced phase), to indicate delayed phase enhancement [37]. The L/E ratio and histological grade of pancreatic fibrosis were correlated with the development of a clinically relevant pancreatic anastomotic failure (PAF) and the other clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Given this situation, it was difficult to obtain as reliable result as was expected using the arterial image data. Meanwhile, in order to express the delayed enhancement corresponding to pancreatic fibrosis, we used a 3-min delayed CT attenuation value after contrast administration, and calculated two enhancement ratios, (EP–Pre)/Pre and (EP–Pre)/(AP–Pre), while previous studies mentioned above used CT attenuation values of hepatic or portal-venous phases 60–70 sec after the administration of the contrast material [14,37]. In most studies, the time-attenuation curve showed a plateau or gradual slope during the 3-min delay after contrast administration with higher attenuation values in the fibrotic pancreas compared to those in the normal pancreas [15,17,18,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The most powerful and promising imaging modalities were ARFI elastography [35,36], which provides information about the elastic properties of the pancreas; contrast-enhanced CT, which reflects the enhancement characteristics of the pancreatic parenchyma; [37,38] MR images, which display the ratios of the signal intensity of the pancreas relative to hepatic, splenic, or muscular values on T1-weighted MRI [43,44], and time-signal intensity curves on dynamic contrast-enhanced MRI [18,46,47,49], in which the MR images reflect the histological degree of pancreatic fibrosis; and MDCT and/or MRI, which reflect the histological grade of pancreatic fatty infiltration [40,41,51]. US elastography, with either a transabdominal or an endoscopic approach, can be a useful, convenient, and inexpensive imaging tool in the diagnostic workup for various pancreatic pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto et al [37] conducted a dual-phase contrast-enhanced CT examination on the pancreas upstream of a tumor in 157 consecutive patients who underwent PD for various periampullary diseases, mainly pancreatic head cancer, to obtain pancreatic CT attenuation in the pancreatic (early phase) and hepatic (late phase) imaging phases. They found that the ratio of the mean CT attenuation value (hepatic to pancreatic phase: late/early [L/E] ratio) correlated positively with the histological degree of fibrosis measured at the pancreatic stump, and the L/E ratio was significantly lower for patients with clinically relevant POPF (0.86 ± 0.14, n = 21) than for those without POPF (1.09 ± 0.24, n = 136; p < 0.0001); a 0.1-U increase in the L/E ratio reduced the odds of POPF by 54%.…”
Section: Ct Studiesmentioning
confidence: 99%